Does Built Environment Matter to Early Adolescents' Physical Activity?. (November 2014) - Lin, Jen-Jia; Ting, Tzu-Cheng
This study examined the relationship of built environments to physical activity among adolescents aged 12 to 14 years old. The study sample included 269 junior high school students studying in Nangang District, Taipei, Taiwan. Sample physical activity data were obtained by surveying adolescents using a self-administered short version of the International Physical Activity Questionnaire (IPAQ) in 2010-2011; the data on built environment came from statistical reports and a geographic information system. The frequency, duration, and meeting guidelines of physical activity were analyzed using various econometric methods. Analytical results demonstrate built environment attributes related to physical activity of adolescents. Compared with previous Western studies, the findings of this study regarding transportation activity mirrored and differed from those of previous studies, while the findings regarding leisure activity differed from those of previous studies. Safety concerns are more essential than convenience concerns for an adolescent engaged in physical activity for leisure in Taipei. The above findings can also happen in other East Asian cities with similar cultural contexts.